In Search of a Rationale for Differentiated Environmental Taxes - Thomas F. Rutherford; Christoph Böhringer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
Environmental tax schemes in OECD countries often involve tax rates differentiated across industrial, commercial and household sectors. In this paper, we investigate four potentially important arguments for these deviations from uniform taxation: pre-existing tax distortions, domestic equity concerns, global environmental effectiveness, and strategic trade policy. Our primary objective is to ascertain whether the degree of tax differentiation observed in many countries can be rationalized on economic grounds. In simulations with a computable general equilibrium model, we calculate optimal policies under various settings. Our simulation results lead us to conclude that there is little economic rationale for the common policy practice of discriminating strongly in favor of heavy industries, even when accounting for interacting taxes, distributional concerns, leakage, and international market power.
Keywords: R13; H21; Q4; C68; 330; optimal environmental taxation; computable general equilibrium; Ökosteuer; Umweltabgabe; Steuerbegünstigung; Optimale Besteuerung; Industrie; Privater Haushalt; Steuerwirkung; Steuerinzidenz; Allgemeines Gleichgewicht; Theorie